Suppression of tumour-specific CD4+ T cells by regulatory T cells is associated with progression of human colorectal cancer. Issue 8 (29th December 2011) - Betts, Gareth; Jones, Emma; Junaid, Syed; El-Shanawany, Tariq; Scurr, Martin; Mizen, Paul; Kumar, Mayur; Jones, Sion; Rees, Brian; Williams, Geraint; Gallimore, Awen; Godkin, Andrew
Abstract : Background: There is indirect evidence that T cell responses can control the metastatic spread of colorectal cancer (CRC). However, an enrichment of CD4 + Foxp3 + regulatory T cells (Tregs) has also been documented. Objective: To evaluate whether CRC promotes Treg activity and how this influences anti-tumour immune responses and disease progression. Methods: A longitudinal study of Treg activity on a cohort of patients was performed before and after tumour resection. Specific CD4 + T cell responses were also measured to the tumour associated antigens carcinoembryonic antigen (CEA) and 5T4. Results: Tregs from 62 preoperative CRC patients expressed a highly significant increase in levels of Foxp3 compared to healthy age-matched controls (p=0.007), which returned to normal after surgery (p=0.0075). CD4 + T cell responses to one or both of the tumour associated antigens, CEA and 5T4, were observed in approximately two-thirds of patients and one third of these responses were suppressed by Tregs. Strikingly, in all patients with tumour recurrence at 12 months, significant preoperative suppression was observed of tumour-specific (p=0.003) but not control CD4 + T cell responses. Conclusion: These findings demonstrate that the presence of CRC drives the activity of Tregs and accompanying suppression of CD4 + T cell responses to tumour-associated antigens. Suppression is associated with recurrence of tumour at 12 months, implying that Tregs contribute to disease progression. These findings offer a rationale for the manipulation of Tregs for therapeutic intervention.